THE IMPLEMENTATION OF TOTAL PHYSICAL RESPONSE (TPR) TO IMPROVE STUDENT’S ENGLISH VOCABULARY DURING PANDEMIC - Ekawati, Anita Dewi (ENGLISH JOURNAL, 2022)
The government’s policy for students to study from home during the Covid-19 pandemic has had a major adjustment impact for students, teachers and parents. Closer collaboration is needed to support the achievement of learning targets. The selection of the right learning method also has an important role in making it easier for students to absorb information and helping teachers and parents as facilitators. In teaching English to kindergarten students, Total Physical Response (TPR) is one method that can be applied. TPR was applied to Kindergarten (TK) Aisyiyah 101 students in class. Fifteen students became respondents in this study. Research data were collected from observations, documentation, interviews, and questionnaires. The results of the study were described using a qualitative descriptive method. From the research data, it can be concluded that TPR facilitates students, teachers, and parents in learning English during studying from home or in Indonesian called as Belajar Dari Rumah (BDR). By using TPR, students can learn with pleasure and absorb information quickly. In addition, TPR also makes it easier for parents and teachers to teach English to children.